The effect of the MIG welding technique on the tensible strength results for cross members making in electric cars with ST 60 materials - Mahendra Cahya Nugraha; Samsudi Samsudi (Journal of Engineering and Applied Technology, 2022)
This study aims to determine the chemical composition and tensile strength of ST60 materials in MIG (Metal Inert Gas) welding for the manufacture of electric car cross members and to reveal the effect of the welding technique on the welding results. The material was medium carbon steel with a thickness of 5 mm for each. The welding was done with MIG welding using a single 90-degree V joint with a current of 150 A. The welding techniques were straight, circular, and zigzag. The results showed a significant effect in circular welding with the largest average of 152,314 kg/mm2, while straight welding showed the lowest average tensile strength of 373.793 kg/mm2. The circular welding also had the strength value with the highest tensile strength of 526,107 kg/mm2.